A Study on Policyholders’ Satisfaction of Health Insurance with Special Reference to Ernakulam District, Kerala - Vijay, Arun; Krishnaveni, V (International Journal of Engineering and Technology, 2018)
Customer satisfaction plays a pivotal role in insurance business, especially health insurance business segment. It is not only indicative of customer loyalty but also helpful in identifying the needs of the customer. Unlike any other forms of insurance health insurance is most complex. Apart from the insurer and the insured, there are various components involved in health insurance mechanism such as healthcare providers like hospitals, Third Party Administrators, etc. So, customer satisfaction has a huge role in health insurance mechanism. It is important to retain the existing customer rather than attracting a new customer in the health insurance business segment, since the marketing cost and efforts required in retaining the existing customer will be less. Since private sector companies are coming out with innovative products in health insurance sector, public sector companies are facing a stiff competition. The study focuses on the customer satisfaction level of health insurance policyholders in Ernakulam district in Kerala. Since health insurance policies are based on yearly renewal basis, customer satisfaction has a lead role to play in determining the renewal of policies with the existing insurance company.Â Â